Beban Kerja dan Fleksibilitas Kerja Terhadap Kepuasan Kerja dengan Motivasi sebagai Pemediasi - Tetty H Sitorus; Harlyn L Siagian (Journal of Management and Bussines (JOMB), 2023)
The research aims to examine the effect of workload and work flexibility on job satisfaction, with motivation as a mediator. The research method uses qualitative with an explanatory approach. The results showed that workload and motivation had a positive effect on job satisfaction, but work flexibility had no effect on job satisfaction. Workload and work flexibility influence motivation. if it is mediated by motivation then workload does not affect job satisfaction but Job Flexibility influences job satisfaction. Simultaneous tests show that Workload and Work Flexibility have a positive effect on Job Satisfaction mediated by motivation. So to achieve the targets that have been set, the company assigns workload to employees. However, heavy workloads can affect employees' physical and emotional well-being. In conclusion, companies need to set work standards and provide work flexibility to increase employee job satisfaction. Employee job satisfaction is very important because it will affect their performance. One aspect that can increase job satisfaction is motivation. Keywords: Workload, Work Flexibility, Job Satisfaction, Motivation